PENGEMBANGAN MEDIA INTERAKTIF SIPEDA SISTEM PEREDARAN DARAH MANUSIA UNTUK MENINGKATKAN BERPIKIR KRITIS - Nur Laili; Supriyono Koeshandayanto; Aynin Mashfufah (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2024)
Student interest in learning science needs to be increased by facilitating students in the learning process so that learning is interesting and learning goals are achieved according to national education goals, one of which is increasing the ability to think critically. There is still a low level of critical thinking and media that supports improving students’ critical abilities. So, media is needed that can provide a breakthrough for these problems. The purpose of this study is to develop media in the form of an android application called SIPEDA by referring to indicators of critical thinking skills for grade V elementary schools. Media development with the Lee and Owens (2004) model. The research subjects consisted of material and media experts, class V teachers, and 22 students for field trials. Quantitative and qualitative data analysis techniques with interview, observation, questionnaire and test methods. The results of the material expert questionnaire got a percentage of 87% with very decent category, media experts got 82.7% of very decent category, the questionnaire for grade V teachers got 85.9% of the very decent category. Field trials with a gain score of 0.59 which means that the media affects critical thinking skills. So, it is concluded that SIPEDA media is feasible and valid to be used in the science learning process of human circulatory system material to improve critical thinking.